Isolation and identification of specific Enterococcus faecalis phage C-3 and G21-7 against Avian pathogenic Escherichia coli and its application to one-day-old geese - Wang, Tianli; Zhang, Ling; Zhang, Yi; Tong, Panpan; Ma, Wanpeng; Wang, Yan; Liu, Yifan; Su, Zhanqiang (Frontiers in Microbiology, 2024)
Colibacillosis caused by Avian pathogenic Escherichia coli (APEC), including peritonitis, respiratory tract inflammation and ovaritis, is recognized as one of the most common and economically destructive bacterial diseases in poultry worldwide. In this study, phages C-3 and G21-7 isolated from sewage around goose farms infected multiple O serogroups (O1, O2, O18, O78, O157, O26, O145, O178, O103 and O104) Escherichia coli (E.coli) with a multiple number of infections (MOI) of 10 and 1, respectively. According to the one-step growth curve, the incubation time of both bacteriophage C-3 and G21-7 was 10 min. Sensitivity tests confirmed that C-3 and G21-6 are stable at 4 to 50 ℃ and pH in the range of 4 to 11. Based on morphological and phylogenetic analysis, phages C-3 and G21-7 belong to Enterococcus faecalis (E. faecalis) phage species of the genus Saphexavirus of Herelleviridae family. According to genomic analysis, phage C-3 and G21-7 were 58,097 bp and 57,339 bp in size, respectively, with G+C content of 39.91% and 39.99%, encoding proteins of 97 CDS (105 to 3,993 bp) and 96 CDS (105 to 3,993 bp), and both contained 2 tRNAs.Both phages contained two tail proteins and holin-endolysin system coding genes, and neither carried resistance genes or virulence factors. Phage mixture has a good safety profile and has shown good survival probability and feed efficiency in both treatment and prophylaxis experiments with day-old geese. These results suggest that phage C-3 and G21-7 can be used as potential antimicrobials for the prevention and treatment of APEC.